2009
DOI: 10.1128/mcb.00997-08
|View full text |Cite
|
Sign up to set email alerts
|

Weak but Uniform Enrichment of the Histone Variant macroH2A1 along the Inactive X Chromosome

Abstract: We studied the enrichment and distribution of the histone variant mH2A1 in the condensed inactive X (Xi) chromosome. By using highly specific antibodies against mH2A1 and stable HEK 293 cell lines expressing either green fluorescent protein (GFP)-mH2A1 or GFP-H2A, we found that the Xi chromosome contains ϳ1.5-fold more mH2A1 than the autosomes. To determine the in vivo distribution of mH2A1 along the X chromosome, we used a native chromatin immunoprecipitation-on-chip technique. DNA isolated from mH2A1-immunop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 35 publications
5
39
0
6
Order By: Relevance
“…Detection of macroH2A was less efficient and at the final time point we detected clear macroH2A foci in only 30% of the cells, compared with over 70% for Ash2l. This could be due to a less prominent enrichment of macroH2A on the Xi over the nuclear average (Mietton et al, 2009). The number of cells showing macroH2A enrichment increased with slower kinetics than did that of Saf-A and Ash2l, and reached a maximum between days 4 and 8 (Fig.…”
Section: Concurrent Recruitment Of Ash2l and Saf-a By Xist In Es Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of macroH2A was less efficient and at the final time point we detected clear macroH2A foci in only 30% of the cells, compared with over 70% for Ash2l. This could be due to a less prominent enrichment of macroH2A on the Xi over the nuclear average (Mietton et al, 2009). The number of cells showing macroH2A enrichment increased with slower kinetics than did that of Saf-A and Ash2l, and reached a maximum between days 4 and 8 (Fig.…”
Section: Concurrent Recruitment Of Ash2l and Saf-a By Xist In Es Cellmentioning
confidence: 99%
“…PcG proteins have been implicated in the maintenance of X inactivation in keeping with their well-established function in maintaining repression of developmental control genes (Wang et al, 2001). Factors that contribute to maintaining the silent state of the Xi further include the histone variant macroH2A (Costanzi and Pehrson, 1998;Mermoud et al, 1999;Mietton et al, 2009;Rasmussen et al, 2000), histone H4 hypoacetylation (Keohane et al, 1996) and DNA methylation (Sado et al, 2000;Sado et al, 2004). Recently, it has been shown that the Smchd1 protein is required for the maintenance of DNA methylation patterns and gene repression on the Xi (Blewitt et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…MacroH2A1 is enriched on the inactive X chromosome (Xi) in mammals, and has been postulated to play an important, but unknown, role in the repression of gene expression associated with X inactivation (Ladurner 2003). Importantly, macroH2A1 has also been found in a variety of contexts on autosomes (Zhang et al 2005;Agelopoulos and Thanos 2006;Changolkar and Pehrson 2006;Choo et al 2006;Buschbeck et al 2009;Mietton et al 2009). Although recent studies have suggested a role for macroH2A1 in autosomal gene regulation (Zhang et al 2005;Agelopoulos and Thanos 2006;Changolkar and Pehrson 2006;Choo et al 2006;Changolkar et al 2007Changolkar et al , 2008Bernstein et al 2008;Buschbeck et al 2009), many questions about the role of macroH2A1 in the regulation of autosomal genes remain.…”
mentioning
confidence: 99%
“…E-mail: tsado@nara.kindai.ac.jp macroH2A2 is encoded by H2afy2. These are enriched on Xi in a chromosome-wide fashion and form a macro chromatin body (Chadwick and Willard, 2001;Costanzi and Pehrson, 2001;Mietton et al, 2009). Their recruitment occurs at the morula stage during mouse development (Costanzi et al, 2000), and at a relatively late phase in the process of X-inactivation during embryonic stem (ES) cell differentiation (Mermoud et al, 1999;Pullirsch et al, 2010).…”
Section: Macroh2a and Parp1mentioning
confidence: 99%